The transformation in Malaysia's 12th general election: The end of National Front Hegemony - Ahmad, N.S.Y. (2009)
The ruling party Barisan Nasional (National Front) inherited the trust and tradition initiated by the Alliance Party that achieved the Malayan Independence. The Alliance first test was the Kuala Lumpur Municipal Council's election in 1952 where they won convincingly 12 out of 14 seats. The support continued in the 1955 General Election, where they won 51 out of 52 seats contested. Nevertheless in the 1969 election, the Alliance has experienced a major loss when they failed to get the two-third majority and even lost several state governments to the opposition. This party later changed its name into National Front in 1972 and simultaneously expanded their components into a bigger coalition party. It has become a unique political formula in Malaysian politics to reduce politicking and keeping the divided ethnicized parties together. The National Front kept on winning in 1974, 1978, 1982, 1986, 1990, 1995, 1999 and 2004 elections handsomely. The dominance of National Front in most General Elections proved that its strength cannot be challenged easily. The supremacy however, started to deteriorate in the 2008 recent General Election when the two-third usual majority was suddenly denied. The ability of the opposition to deny National Front its majority has put the National Front into a very difficult position. Using Gramscian concept of hegemony, this paper tries to elaborate how National Front has successfully maintained their power until suffering big loss in 2008.